THE ROLE OF ULAMA AND MUSLIMS IN STRENGTHENING NATIONAL UNION OF THE REPUBLIC OF INDONESIA (The Government of the Republic of Indonesia) - -, Taufiqurokhman (Department of Government, FISIP, Universitas Padjadjaran, 2017)
The Indonesian government with the central position of power in Java and the form of the Government of the Unitary State of the Republic of Indonesia (NKRI), the spread of Islam in the Land of Java in the framework of NKRI Government implemented by the scholars of Indonesia especially the spread of Islam carried out widely with the appearance of Wali Songo in Java. The presence of the scholars by giving his dakwah to the wider community, and the state of Indonesia is the largest adherents of Islam. At the end of 2014 came the figure of President Jokowi is quite phenomenal and assume the role of President Jokowi many do the ways of Islamic dawah as did the scholars and guardians songo. Namely break through the customs of feudalism culture, like done by the scholars and guardian songo who plunge into the community perform dawah. Judging from the track record of the political journey Jokowi Government which he lived with blusukan leadership model, which is closer to the small community, has led Jokowi in the highest seat of leadership, namely the president of the VII of the Republic of Indonesia. Therefore, this scientific paper, will explore and analyze the role of ulama in strengthening the government of the Republic of Indonesia, which is commanded by President Jokowi, the president of Indonesia to VII, So that can be seen how far the alignment of scholars and Muslims in Indonesia. Questions in the formulation of the problem in this writing is the role of scholars and Muslims in the Government of NKRI. Type of research used to answer these questions is the type of library research (library research), with the nature of descriptive analytic research with socio-political approach. Data obtained from journal books, laws, documentation, research reports and other sources relevant to the studied discussion. After all the data collected, then the next step is to analyze the data with explorative deductive analysis, that is how the political behavior of President Joko Widodo in his role against Muslims led by the scholars in Indonesia. After conducting a study of the data, this study drew the conclusion of a leaders social behavior affecting the government of his dreams. As in the case studied in this study, it was found that the role of scholars and Muslims has a strong influence to strengthen the government of the Unitary Republic of Indonesia. gb777